BIAS GENDER DALAM BUKU TEKS PELAJARAN BAHASA INDONESIA SEKOLAH MENENGAH ATAS - Dewi Ulfah; Idawati Garim; Sultan Sultan (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
Abstract: Gender Bias in Indonesian Language Textbook in Senior High School.This research to described gender bias based on the subject-object viewpoint and author-reader viewpoint of Sara Mills theory on textbook. The data of this research are vocabulary, clause, sentence, or paragraph that contain gender perspective and the source of the data of this research is reading text on the Indonesian language textbook for senior high school grade X by Kemendikbud, revised edition of 2017. Technique of data collection are reading and writing. The whole data collected were analyzed in depth and identified based on gender perspective. The results of this research are (1) forms of gender bias of the subject-object viewpoint are subordination and stereotyped to women, (2) forms of gender bias of the author-reader viewpoint, there are two aspects of the findings, namely indirect sweeping carried out by means of mediation and cultural code. Direct sweeping which uses first-person singular pronoun, third-person singular pronoun, and third-person plural pronoun.